High EVI1 Expression Predicts Adverse Outcomes in Children With De Novo Acute Myeloid Leukemia - Yongzhi Zheng; Yan Huang; Shaohua Le; Hao Zheng; Xueling Hua; Zaisheng Chen; Xiaoqin Feng; Chunfu Li; Mincui Zheng; Honggui Xu; Yingyi He; Xiangling He; et al. (Frontiers in Oncology, 2021)
BackgroundA high ecotropic viral integration site 1 (EVI1) expression (EVI1high) is an independent prognostic factor in adult acute myeloid leukemia (AML). However, little is known of the prognostic value of EVI1high in pediatric AML. This study aimed to examine the biological and prognostic significance of EVI1high in uniformly treated pediatric patients with AML from a large cohort of seven centers in China.MethodsA diagnostic assay was developed to determine the relative EVI1 expression using a single real-time quantitative polymerase chain reaction in 421 newly diagnosed pediatric AML patients younger than 14 years from seven centers in southern China. All patients were treated with a uniform protocol, but only 383 patients were evaluated for their treatment response. The survival data were included in the subsequent analysis (n = 35 for EVI1high, n = 348 for EVI1low).ResultsEVI1high was found in 9.0% of all 421 pediatric patients with de novo AML. EVI1high was predominantly found in acute megakaryoblastic leukemia (FAB M7), MLL rearrangements, and unfavorable cytogenetic aberrance, whereas it was mutually exclusive with t (8; 21), inv (16)/t (16; 16), CEBPA, NPM1, or C-KIT mutations. In the univariate Cox regression analysis, EVI1high had a significantly adverse 5-year event-free survival (EFS) and overall survival (OS) [hazard ratio (HR) = 1.821 and 2.401, p = 0.036 and 0.005, respectively]. In the multivariate Cox regression analysis, EVI1high was an independent prognostic factor for the OS (HR = 2.447, p = 0.015) but not EFS (HR = 1.556, p = 0.174). Furthermore, EVI1high was an independent adverse predictor of the OS and EFS of patients with MLL rearrangements (univariate analysis: HR = 9.921 and 7.253, both p < 0.001; multivariate analysis: HR = 7.186 and 7.315, p = 0.005 and 0.001, respectively). Hematopoietic stem cell transplantation (HSCT) in first complete remission (CR1) provided EVI1high patients with a tendential survival benefit when compared with chemotherapy as a consolidation (5-year EFS: 68.4% vs. 50.8%, p = 0.26; 5-year OS: 65.9% vs. 54.8%, p = 0.45).ConclusionIt could be concluded that EVI1high can be detected in approximately 10% of pediatric AML cases. It is predominantly present in unfavorable cytogenetic subtypes and predicts adverse outcomes. Whether pediatric patients with EVI1high AML can benefit from HSCT in CR1 needs to be researched further.